Socio-demographic and clinical patterns of patients with obstructive airway disease - Adnan, Khondekar Mustaq; Sejooti, Shabnam Sarwar; Ashrafuzzaman, Mohammad (International Journal of Advances in Medicine, 2021)
Background: Obstructive airway disease (OAD) includes two entities that share many common characteristics. Those are asthma and chronic obstructive pulmonary disease (COPD). On the other hand, in our regular practice, we observe that psychiatric symptoms of anxiety, depression, and cognitive dysfunction often occur in patients suffering from such diseases which are also associated with their socio-demographic and clinical status. Aim of the study: The aim of this study was to determine the socio-demographic and clinical status of patients with OAD. Methods: This was a cross-sectional observational study which was conducted at the department of respiratory medicine in the national institute of diseases of the chest and hospital, Dhaka, Bangladesh during the period from March 2018 to February 2019 in collaboration with the department of pathology, radiology, and respiratory laboratory. A total of 160 cases of asthma or COPD were enrolled in this study. Statistical analyses of the results were obtained by using Windows-based computer software devised with statistical packages for social sciences (SPSS-23.0). Results: A total number of 160 patients were selected and the mean age of the total participants was 53.0±14.0 years. In this study, the male-female ratio of the study people was 1.13:1. The majority (91.2%) of patients were married. Almost three fourth (73.7%) of patients were from rural areas. Almost one-third (31.9%) of patients completed primary education level. The majority (27.5%) of the patients were service holders. The average monthly income was 1871.9±4888.8 taka. Almost two-thirds (66.3%) of patients were smokers. In total 98 (61.3%) patients had COPD and 62 (38.7%) had asthma. In this study in total 98 (61.3%) patients had COPD and 62 (38.7%) had asthma. Among 98 COPD patients 10 (10.2%) had mild, 29 (29.6%) had moderate, 40 (40.8%) had severe and 19 (19.4%) had very severe COPD. Among 62 asthmatic patients 22 (35.5%) had mild, 16 (25.8%) had moderate, 11 (17.7%) had severe and 13 (21.0%) had very severe asthma. Conclusions: According to the findings of this study we can conclude that the frequency of OAD is higher among aged, smokers, married male people than others. The ratio of COPD patients may be higher than asthmatic patients among the rural population of Bangladesh. The mean depression inventory score was found to some higher among asthmatic patients than that of COPD patients.